2009
DOI: 10.1021/ci900309s
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Library Enumeration and Lead Hopping using Comparative Interaction Fingerprint Analysis and Classical 2D QSAR Methods for Seeking Novel GABAA α3 Modulators

Abstract: Selective modulators of GABA(A) alpha(3) (gamma amino butyric acid alpha(3)) receptor are known to alleviate the side effects associated with nonspecific modulators. A follow up study was undertaken on a series of functionally selective phthalazines with an ideological credo of identifying more potent isofunctional chemotypes. A bioisosteric database enumerated using the combichem approach endorsed mining in a lead-like chemical space. Primary screening of the massive library was undertaken using the "Miscreen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…The theoretical precondition for such modification was the methodology of bioisosteric replacements widely and effectively used by modern medical chemistry, involving the replacement of one group in the molecule close to it by the properties [11,12]. It should be remembered that the bioisosteric groups are groups that are the same not only in size or volume, but have similar physical and chemical properties, and therefore, reveal a similar pharmacological effect [13][14][15].…”
Section: синтез и анальгетические свойства N-(бензил)-2-гидрокси-9-меmentioning
confidence: 99%
“…The theoretical precondition for such modification was the methodology of bioisosteric replacements widely and effectively used by modern medical chemistry, involving the replacement of one group in the molecule close to it by the properties [11,12]. It should be remembered that the bioisosteric groups are groups that are the same not only in size or volume, but have similar physical and chemical properties, and therefore, reveal a similar pharmacological effect [13][14][15].…”
Section: синтез и анальгетические свойства N-(бензил)-2-гидрокси-9-меmentioning
confidence: 99%
“…[50] The SAR report functionality of MOE was used to identify key R-group motifs [51,52] that were structurally transformed using the concept of bioisosterism. [36,53,54] Potential isosters for the marked Markush fragments were identified from a biosisosteric database containing fragments of synthetic tractability using the Brood software. [39] Four classes of isosters that match the query fragments in terms of shape, atom-type, electrostatics, structure, and graph were identified.…”
Section: Bioisterism Guided Virtual Combinatorial Library Enumerationmentioning
confidence: 99%
“…QuaSAR CombiGen module of MOE was then used to enumerate a virtual library of all possible products that could be combinatorially obtained from the set of fragments. [36] The targeted library containing 2,37,720 compounds, thus generated, can be screened en masse and yield better enrichment rates than either a random or diverse library. [55] Markush fragments considered for isosteric replacement are shown in Figure 3 and the core scaffolds used for clipping the fragments are shown in Figure 2.…”
Section: Bioisterism Guided Virtual Combinatorial Library Enumerationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Bayesian approach, on account of the frequency of various descriptors occurrence, is a robust classification methodology which can differentiate actives from inactives [14,16]. Many examples have demonstrated its application in structure-activity analysis and drug discovery [14,[17][18][19][20][21]. Besides, several studies have shown that Bayesian categorization demonstrates higher EF and accuracy than molecular docking in identification of actives from decoys [22].…”
Section: Introductionmentioning
confidence: 99%